Pengembangan Media Interaktif Berbasis iSpring Presenter pada Materi Bahasa Arab Madrasah Ibtidaiyah - Risa Gowwiyuningsih (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2023)
The use of learning media that has been applied so far still has various shortcomings, both in terms of design, material, and language. Based on these problems, the author formulates the research problem, namely: "How is the development process, level of feasibility, and student response to the PowerPoint iSpring Presenter learning media on vocabulary material?" This study aims to develop learning media based on PowerPoint iSpring Presenter on vocabulary material and to determine the feasibility, effectiveness, and student response to the media. This study uses the Research and Development (R&D) method by adapting the development model from Borg & Gall. Data collection techniques are carried out through questionnaires and interviews. Based on the results of research conducted at MI Muhammadiyah Krakitan, it was obtained that the development of PowerPoint iSpring Presenter media includes three main aspects, namely design, material, and language. The validation results from the media expert team showed an average percentage of 84%. Validation from the material expert team obtained an average of 89%, and validation from the language expert team reached an average of 92%. Student responses to the appeal of learning media, based on small-scale trials, obtained an average score of 86.5% with the interpretation category "Very Interesting". In large-scale trials, the average score increased to 95.7% with the category “Very Interesting”. Meanwhile, the response from educators as media users showed an average score of 86% with the interpretation category “Very Appropriate”.